Standardization of dehydration techniques for vegetable type cluster bean (Cyamopsis tetragonoloba L.) (Current Horticulture, 2024)
An experiment was conducted to standardized dehydration techniques for cluster bean (Cyamopsis tetragonoloba L.) pods at  ICAR-CIAH, Bikaner during 2020-21. The pods were blanched for different durations (3, 4, 5, 6 and 7 minutes) in boiling water to  standardize blanching process. Five minutes blanching in boiling water followed by immediate dipping in cold water was found  optimum for getting quality dehydrated product. Blanching treatment significantly enhanced the drying (5.67) and rehydration  rate (4.65) and augmented rehydration capacity of dried pods. The dehydration recovery was 21.24% of fresh pods. The dried  samples stored with HDPE pouches had low moisture content and high rehydration capacity than the samples stored with  LDPE pouches. Thus, it is recommended that blanching is an essential process for quality pods. The HDPE pouches were found  suitable packaging material for storage stability of dried pods.
Keywords: Dehydration; Blanching; LDPE; HDPE; Cyamopsis tetragonoloba L.